Chlorotoxin-conjugated graphene oxide for targeted delivery of an anticancer drug - Wang H (Dove Medical Press, 2014)
Hao Wang,1 Wei Gu,2 Ning Xiao,2 Ling Ye,2 Qunyuan Xu1 1Regeneration and Repair, Key Laboratory for Neurodegenerative Disease of The Ministry of Education, 2School of Chemical Biology and Pharmaceutical Sciences, Capital Medical University, Beijing, People's Republic of China Abstract: Current chemotherapy for glioma is rarely satisfactory due to low therapeutic efficiency and systemic side effects. We have developed a glioma-targeted drug delivery system based on graphene oxide. Targeted peptide chlorotoxin-conjugated graphene oxide (CTX-GO) sheets were successfully synthesized and characterized. Doxorubicin was loaded onto CTX-GO (CTX-GO/DOX) with high efficiency (570 mg doxorubicin per gram CTX-GO) via noncovalent interactions. Doxorubicin release was pH-dependent and showed sustained-release properties. Cytotoxicity experiments demonstrated that CTX-GO/DOX mediated the highest rate of death of glioma cells compared with free doxorubicin or graphene oxide loaded with doxorubicin only. Further, conjugation with chlorotoxin enhanced accumulation of doxorubicin within glioma cells. These findings indicate that CTX-GO is a promising platform for drug delivery and provide a rationale for developing a glioma-specific drug delivery system. Keywords: glioma, nanosheet, pH-dependent, cytotoxicity